The Outcome of Direct-Acting Antivirals in Treatment-Naïve Non-Cirrhotic, Chronic Hepatitis-C Infected Patients in a Tertiary Care Center (Academia Journal of Medicine, 2021)
Background: To determine the outcome of Direct-Acting Antivirals in treatment-naïve Non-Cirrhotic, Chronic Hepatitis-C infected patients in a tertiary care Centre. Subjects and Methods: Hepatitis C positive non cirrhotics patients were included in the study. Treatment was given according to HCV Genotype and HCV Viral Load. 12 weeks after completion of treatment with Direct-acting antivirals patient were assessed for the Sustained Virological Response (SVR) ie.;SVR12. Results: The (Mean±SD) age was found to be 43.92±13.51 years. There are 11(44%) male whereas 14(56%) female. Out of total subjects, 3(12%) had diabetes mellitus whereas 5(20%) reported hypertension. Genotype 3 was found to be most common (72%). The mean±SD after treatment A.L.T U./L, A.S.T U/.L and I.N.R observed was 13.95±4.90, 14.97±5.03 and 1.40±0.54 respectively. The mean±SD Total Bilirubin mg/dL, Albumin g/dL and Hb g/dl observed was 0.72±0.32, 3.99±0.57 and 11.49±1.46 respectively. In 23 (92%) subjects S.V.R was achieved whereas in 2(8%) cases it was not achieved. Conclusion:Oral D.A.A accomplished higher SVR12 rates and were very much endured in this cohort based study associated with patients diagnosed with Chronic Hepatitis-C.
Keywords: Antiviral therapy; Non-Cirrhotic; Chronic Hepatitis-C